THE CONSUMER ACCEPTANCE TOWARD CARP FISH (Cyprinus carpio) NANIURA WITH DIFFERENT JUNGGA LIME (Citrus hytrix DC) - Pasaribu, Rollen M; Sari, N Ira; ', Edison (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research held on january 2015 at Technology of Result FisherLaboratory, Chemical of Result Fishery, Fisheries and marine science faculty,Riau university. This research aims to understand consumer acceptance towardCarp fish (Cyprinus carpio) naniura with different Jungga Lime. The researchmethod used experiment method, that was do carp fish naniura produceexperiment series with different jungga lime. The design was completelyrandomized design non factorial that was addition of different jungga lime consistfrom 3 degree that were jungga lime 110 ml (A1), 130 ml (A2), 150 ml (A3) in 3hours fermentation with 9 fish. The result of this research showed the most likeorganoleptic by consumer was jungga lime 110 ml (A1) with average preferencevalue ( 3,15 ), taste ( 3,04) aroma ( 3,24), texture ( 3,07), water content ( 73, 91),protein content ( 11,51), fat content ( 2,75), pH value ( 6,70).Keywords: Jungga lime, carp fish (Cyprinus carpio), consumer acceptance